The comprehensive evaluation and mechanism of HOUTTUYNIA CORDATA (Thunb) injection as a complementary therapy for infantile pneumonia - Jincheng Du; Shibin Tian; Mengyue Liu; Jiahuan Li; Zhijian Long (Phytomedicine Plus, 2024)
Background: Houttuynia cordata injection (HCI), a commercialized product made from the active ingredients extracted from Houttuynia cordata Thunb, has been used clinically in China for >50 years with significant therapeutic effects on pseudorabies herpesvirus infection in vitro and H1N1 influenza virus in mice. Purpose of study: This work is to evaluate the complementary therapeutic effect of HCI on infantile pneumonia (IP) and to explore its mechanism of action. Study design: First, the complementary efficacy of HCI in improving IP was evaluated by meta-analysis, with only randomized controlled trials from 5 electronic databases were included in this study. Second, network pharmacology was employed to predict the underlying mechanism of HCI in improving IP. Finally, molecular docking, surface plasmon resonance (SPR) and lipopolysaccharide (LPS)-induced rat IP model were used to verify the predicted results. Results: Meta-analysis indicated that HCI can complementarily improve pneumonia by increasing cure rate and reducing the duration of fever, cough, and wheezing. Network pharmacology analysis using databases such as Traditional Chinese Medicine Systems Pharmacology (TCMSP), Swiss target prediction, Therapeutic target database and Genecards showed that quercetin, houttuynin and kaempferol in HCI are the main compounds that improve IP and regulate 96 pneumonia-related protein targets. Protein-protein interaction (PPI) network analysis indicated that interleukin-6, tumor necrosis factor α (TNF-α), interleukin-1 β (IL-1β), protein kinase B-1, matrix metalloproteinase 9, interleukin-10, tumor protein 53, epidermal growth factor receptor, C-X-C motif chemokine 8 and interferon gamma are the ten most relevant targets of HCI in improving IP. In the gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis, 96 targets are involved in 706 GO functions and 148 KEGG pathways. Among them, TNF-α/IL-1β signaling associated with inflammatory response is considered to be an important mechanism in IP. Molecular docking, SPR and LPS-induced IP model confirmed the predicted results. Conclusions: HCI has a complementary therapeutic effect on IP, and its mechanism may be related to the inhibition of TNF-α/IL-1β inflammatory response by two flavonoid compounds.